종골 골절의 제한적 후방 접근법 수술적 치료 후 조기 운동 및 재활 치료의 결과 - 송경원; 김갑래; 이진영; 이광남; 서은호; Song, Kyung-Won; Kim, Gab-Lae; Lee, Jin-Young; Lee, Kwang-Nam; Seo, Eun-Ho (대한족부족관절학회지, 2008)
Purpose: To evaluate the result of the early exercise and rehabilitation after limited posterior operative treatment of the calcaneal fractures. Materials and Methods: Between May 2005 and December 2007, 43 cases with intraarticular calcaneal fractures were treated by open reduction with K-wires and Steinmann pins. Mean age and mean follow-up period were 42.5 years old and 15 months. All patients were treated with the same postoperative protocol, the early exercise of subtalar joint without short leg splint and cast was began after postoperative 1 day, non-weight bearing crutch ambulation did after 2 weeks, partial-weight bearing crutch ambulation did after 6 weeks, without crutch ambulation did after 10 weeks. The fractures was classified by Essex-Lopresti and Sanders classification using radiographs and the functional outcomes were evaluated by circle draw exercise, AOFAS score. Results: By Essex-Lopresti classification, the tongue type was 6 cases (14%), the joint depression type was 15 cases (35%), the combined type was 22 cases (51%). By Sanders classification, type II were 10 cases (23%), type III were 15 cases (58%), and type IV were 8 cases (19%). By AOFAS functional evaluation, the mean preoperative scores were 70.3 and 70.5 respectively, mean postoperative scores were 83.7 and 86.9 respectively. There were satisfactory results in 40 cases but 3 cases were unsatisfactory including on case of lateral impingement and 2 cases of traumatic arthritis of subtalar joint. Conclusion: We obtained satisfactory result of the early exercise of subtalar joint without short leg splint and cast and rehabilitation after limited posterior operative treatment of the calcaneal fractures.